The prognosis for fetuses with Vein of Galen Malformation and symptoms of heart failure - Nawara-Baran, Agnieszka (Prenatal Cardiology, 2017)
Vein of Galen Malformation (VGM) it is the most common cerebral arteriovenus malformation in fetuses and children. Usually VGM causes volume overload of the heart and can induce mass effect in the brain, causing progressive neurological impairment. Modern treatment allow on earlier therapy (before the 5th monthof life). This gives the newborn with isolated VGM and heart failure a chance of survival. This work presents case of isolated vein of Galen malformation with diagnosed cardiomegaly, monophasic flow through the tricuspid valve, large right heart, pericardiac effusion, dilatation of SVC and abnormal doppler exam. Postnatal management included aggressive medical treatment of cardiac failure and early transarterial embolization of the selected vessels feeding the aneurysm at 6 days of age. The newborn is 6 month old, growing normally without neurological deficits or developmental retardation and waiting of next stage therapy. New techniques of treatment give fetuses with VGM and prenatal signs of cardiac insufficiency a chance of survival and healthy life, in a group of selected cases. The analysis of the cardiovascular system in fetuses with VGM according to uniform criteria is essential in order to assess the influence of these malformations on the survivability of newborns.